EFFECT OF DIFFERENT FERTILIZER RATE ON BIOLOGICAL PRODUCTIVITY AND WATER QUALITY OF ACID SULFATE SOILS FISHPOND (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2010)
An experiment was conducted in order to evaluate the effect of differentfertilizer regimes on biological productivity and water quality of limed acid sulfatesoils fishponds. The experiment consisted of 4 different fertilizer treatments i.e.,control without fertilizer input, chicken manure 50 g/m2 /week, chicken manure 75 g/m2 /week, and inorganic fertilizer (6 g of urea + 3.5 g of TSP /m /week), eachtreatment with 3 replications. Result of experiment shows that Inorganic fertilizationgave the highest chlorophyll a concentrations (83.40 mg/m3), and the highest net fishyields 7.53 kg /ha /day), but had a lower water pH than that in control. Ponds whichare fertilized with chicken manure 75 g /m2 /week gave the highest fish survival rate(100%) while in ponds without fertilizer inputs only 3.3 % of stocked fish wassurvived.